Biofilm characteristics and evaluation of the sanitation procedures of thermophilic Aeribacillus pallidus E334 biofilms. Issue 4 (21st April 2017) - Kilic, Tugba; Karaca, Basar; Ozel, Beste Piril; Ozcan, Birgul; Cokmus, Cumhur; Coleri Cihan, Arzu
Abstract: The ability of Aeribacillus pallidus E334 to produce pellicle and form a biofilm was studied. Optimal biofilm formation occurred at 60 °C, pH 7.5 and 1.5% NaCl. Extra polymeric substances (EPS) were composed of proteins and eDNA (21.4 kb). E334 formed biofilm on many surfaces, but mostly preferred polypropylene and glass. Using CLSM analysis, the network-like structure of the EPS was observed. The A . pallidus biofilm had a novel eDNA content. DNaseI susceptibility (86.8% removal) of eDNA revealed its importance in mature biofilms, but the purified eDNA was resistant to DNaseI, probably due to its extended folding outside the matrix. Among 15 cleaning agents, biofilms could be removed with alkaline protease and sodium dodecyl sulphate (SDS). The removal of cells from polypropylene and biomass on glass was achieved with combined SDS/alkaline protease treatment. Strong A. pallidus biofilms could cause risks for industrial processes and abiotic surfaces must be taken into consideration in terms of sanitation procedures.